(untitled) (Global Journal of Management and Business Research, 2021)
The study examined the impact of land and property based taxation on land resources development in Abeokuta South, Ogun State. The objective is to identify the significant impact of property taxation on land resources development in Abeokuta South and the effectiveness of it in the study area. A quantitative approach was adopted in this study, using questionnaire and a semi structured interview as an instrument for data collection. Seventy-five (75) number questionnaires were administered to valuers in Fifteen (15) Estate Practicing firms in Abeokuta South LGA, while interview was conducted amongst four (4) senior cadre staff at the lands department, in the Bureau of lands and survey. The study revealed that 50% of the respondent which represents the average, opined that the impact of land and property based tax on land resources development is at a low extent. Ignorance on the part of tax payers and government and corrupt practices have been identified as the major cause of the low impact.